2002
DOI: 10.1002/jez.10130
|View full text |Cite
|
Sign up to set email alerts
|

Branchial innervation

Abstract: Inspection of the dorsal end of fish gills reveals an impressive set of nerve trunks, connecting the gills to the brain. These trunks are branches of cranial nerves VII (the facial) and especially IX (the glossopharyngeal) and X (the vagus). The nerve trunks carry a variety of nervous pathways to and from the gills. A substantial fraction of the nerves running in the branchial trunks carry afferent (sensory) information from receptors within the gills. There are also efferent (motor) pathways, which control mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 115 publications
1
67
0
3
Order By: Relevance
“…In other species, intrinsic bipolar neurons innervate the eFA sphincter, thus they are likely to be involved in regulating blood flow through the gill (Jonz and Nurse, 2003). Gill blood flow is modulated during hypoxia by the contraction of the eFA sphincter, which causes an increase in branchial blood pressure, which in turn causes an increase in lamellar recruitment increasing the functional surface area for gas exchange (reviewed by Sundin and Nilsson, 2002). ) and (C) cell length (μm) in Type I cells in various locations in the gill filament of bowfin exposed to normoxia or to sustained hypoxia with or without access to air.…”
Section: Type II Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other species, intrinsic bipolar neurons innervate the eFA sphincter, thus they are likely to be involved in regulating blood flow through the gill (Jonz and Nurse, 2003). Gill blood flow is modulated during hypoxia by the contraction of the eFA sphincter, which causes an increase in branchial blood pressure, which in turn causes an increase in lamellar recruitment increasing the functional surface area for gas exchange (reviewed by Sundin and Nilsson, 2002). ) and (C) cell length (μm) in Type I cells in various locations in the gill filament of bowfin exposed to normoxia or to sustained hypoxia with or without access to air.…”
Section: Type II Cellsmentioning
confidence: 99%
“…Serotonin caused a dilation of the CVS in Atlantic cod (Gadus morhua) (Sundin, 1995), increasing blood flow to the mitochondrion-rich cells. It has also been suggested that dilation of the CVS could divert plasma from the arterio-arterial pathway increasing the haematocrit in the lamellae and improving oxygen uptake (Sundin and Nilsson, 2002), but no anastomoses between these two circulations have been found in bowfin (Olson, 1981). It is also possible that these cells contained synaptic vesicles not labelled by the SV2 antibody.…”
Section: Type III Cellsmentioning
confidence: 99%
“…Gill NECs are characterized by having cytoplasmic synaptic vesicles containing neurotransmitters and are believed to release their contents across a chemical synapse onto afferent nerve terminals (Dunel-Erb et al, 1982;Jonz and Nurse, 2003;Perry et al, 2009). Chemoreceptor responses are then carried from the gills to the central nervous system by afferent fibres of the glossopharyngeal and vagus nerves (Milsom and Brill, 1986;Burleson and Milsom, 1993;Sundin and Nilsson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The carotid body and first gill arch are innervated by the glossopharyngeal (cranial nerve IX) nerve (Sundin and Nilsson, 2002;Gonzalez et al, 1994). The branchial neuroepithelial cells of fish gills are the phylogenetic precursors to glomus (O 2 -sensing cells of the mammalian carotid body.…”
Section: Corneille Heymens Was Awarded the Nobel Prize In Physiology mentioning
confidence: 99%